Kajian Sosiologi Sastra Novel Bidadari Untuk Dewa Karya Asma Nadia : Suatu Tinjauan Sastra: A Sociological Study of Literature in the Novel Bidadari Untuk Dewa by Asma Nadia:A Literary Perspective - Devi, Mutia Sari (Universitas Tidar, 2025)
Asma Nadia published the novel Bidadari Untuk Dewa, which tell the story of Dewa as the main character. Dewa’s honesty and perseverance serve as key traits that help him navigate the challenges of his life. Moreover, Dewa exemplifies how true love can heal wounds, improve economic conditions, and create opportunities for happiness. The author’s writing inspired the researcher to explore the novel using a sociological approach to literature, examining the author’s worldview, social and cultural background, as well as the character and their relationships. The research employs a qualitative descriptive method, producing descriptive data derived from dialogues, monologues, and narratives in the novel Bidadari Untuk Dewa by Asma Nadia. The study findings reveal that Bidadari Untuk Dewa portrays the real-life journey of Dewa as henavigates the challenges of life in Bandung overcoming life’s hardships. Set in Bandung, Dewa consistently applies Islamic values in his life as a way to embrace the destiny ordained by Allah.